Following the rules practical reasoning and deontic constraint - Heath, Joseph, 1967- (Oxford : Oxford University Press, 2008)
For centuries, philosophers have been puzzled by the fact that people often respect moral obligations as a matter of principle setting aside considerations of self-interest. This text shows how rule-following can be understood as an essential element of rational action.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Deontic logic; Practical reason; Ethics; Duty